2021
DOI: 10.3390/nu13082858
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Mortality from Coronary Artery Disease in Sardinia: A Geospatial Analysis

Abstract: The role of water hardness on human health is still debated, ranging from beneficial to harmful. Before the rise of drinking bottled water, it was a common habit to obtain supplies of drinking water directly from spring-fed public fountains. According to the geographic location, spring waters are characterized by a variable content of mineral components. In this ecological study, for the first time in Sardinia, Italy, the spatial association between spring water quality/composition and standardized mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Our findings contribute to the accumulating evidence on the longevity-promoting effects of hard water. Recent examples of such research include studies in China [ 18 ] and Costa Rica [ 19 ] on longevity, and in Sardinia on protective effects against cardiovascular mortality [ 20 ]. In those studies, areas were not specifically geologically characterized; however, our study demonstrated how the limestone bedrock occupancy is related to the hardness of drinking water, which is in turn related to the centenarian rate across the 11 constituent municipalities of our four surveyed islands.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contribute to the accumulating evidence on the longevity-promoting effects of hard water. Recent examples of such research include studies in China [ 18 ] and Costa Rica [ 19 ] on longevity, and in Sardinia on protective effects against cardiovascular mortality [ 20 ]. In those studies, areas were not specifically geologically characterized; however, our study demonstrated how the limestone bedrock occupancy is related to the hardness of drinking water, which is in turn related to the centenarian rate across the 11 constituent municipalities of our four surveyed islands.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of evidence, drinking water has shown numerous potential effects on metabolic and CV health. It was confirmed that slightly alkaline drinking water helps to keep blood vessels elastic and maintain blood pressure, which is beneficial for the CV system [ 39 ]. Alkalization of urine may have an effect on removing uric acid from the body [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that research in recent years has shown that calcium intake from the diet can benefit cardiovascular health. A geospatial analysis found an inverse association between high calcium spring water and cardiovascular mortality, citing waters with high calcium content as cardiovascular protective 36 . Multiple studies on drinking water have found the same result 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%